Analysis of the Influence of Fiscal Capacity and Economic Growth on the Human Development Index - Nur, Syamsir; Arifin, Arifin; Anam, Syamsul (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This study aims to examine the impact of fiscal capacity and economic growth on the Human Development Index (HDI) in Southeast Sulawesi Province during the 2020-2022 period. A quantitative approach was used, using secondary data from the Central Statistics Agency and other relevant sources. The analysis method employed is multiple linear regression to assess the relationship between fiscal capacity, economic growth, and HDI. The analysis results indicate that fiscal capacity does not have a significant partial effect on HDI, with a t-value significance of 0.483 (> 0.05). This suggests that while fiscal capacity exists, the budget allocation has not been effectively channeled toward sectors that directly enhance quality of life, such as education, healthcare, and welfare. On the other hand, economic growth shows a significant positive effect on HDI, with a t-value significance of 0.000 (< 0.05). Economic growth improves the population's access to education, healthcare, and welfare. When considered, fiscal capacity and economic growth have a significant combined effect on HDI, with an F-value significance of 0.000 (< 0.05). However, more than fiscal capacity is needed, likely due to inefficiencies in budget allocation.